EFL TEACHERS’ REFLECTION IN TEACHING ENGLISH TO EFL STUDENTS OF RURAL AREAS - Saiful, Jepri Ali; Triyono, Sulis (International Journal of Language Education, 2018)
Theoretical and empirical grounds suggest that the discussions on the practices of teaching English in rural area are limited in numbers. Ergo the voices, challenges, and recommendations echoed by EFL teachers of rural areas remain unexplored. This study is thus to shed light on the voices, challenges, and recommendations of EFL rural teachers in teaching EFL to students of rural areas. This study used qualitative research method with multiple case study design. The participants were two EFL service teachers teaching English in Pegunungan Bintang in Papua and Talaud Island in North Sulawesi, Indonesia. The data collection techniques were teaching reflection writing journal and phone and WhatsApp call semi-structured interview. This study extended our knowledge that teacher-centered learning was not always perceived to be a left-behind and invaluable teaching approach. This study revealed that teacher-centered learning, which the teachers became the sources of knowledge, was an appropriate teaching approach to teach English to students of rural areas. Moreover, this study found that lack of facilities and learning recourses as well as students’ low motivation and proficiency in English language were main challenges faced by EFL teachers in rural areas. Therefore, shared-recommendations were given by the participants to English teacher candidates taking career to be English teachers in rural areas. First, English teacher candidates should have or build strong and good characters. Meaning, they have to be discipline, creative, innovative, patient, firm and adaptable. These characters are non-negotiable for other English teacher candidates teaching English in any region as well. Second, English teacher candidates should take into account students’ competency and social condition of learning to make students succeed in target language. Third, they had better use teacher talk and caretaker speech to explain English teaching materials or topics to the students.